Effect of two formulations of 10% sodium ascorbate on fracture resistance of endodontically treated tooth submitted to dental bleaching with hydrogen peroxide associated titanium dioxide nanoparticles - Bontorin, Francisco Carlos [UNESP]; Kuga, Milton Carlos [UNESP]; Cioffi, Sabrina Spinelli [UNESP]; Só, Marcus Vinicius Reis; Faria, Gisele [UNESP]; Pereira, Jefferson Ricardo (My University, 2014)
Purpose: This study evaluated the effect of 10% sodium ascorbate (10SA), in gel (10SAg) or aqueous solution (10SAs) formulations, on fracture resistance of endodontically treated tooth submitted to dental bleaching procedures with 15% hydrogen peroxide associated with titanium dioxide (15HP-TiO2) nanoparticles and photoactivated by LED-laser. Material and methods: Forty maxillary premolars were endodontically-treated and embedded in acrylic resin up to the cement-enamel junction. The specimens were divided into four groups (n=10): G1 (negative control): no bleaching, coronal access restored with composite resin; G2 (positive control): three dental bleaching sessions using 15HP-TiO2 and LED-laser photoactivation and restored with composite resin (positive control); G3 (10SAg): similar procedures to G2, but applied 10SA, in gel formulation, for 24 hours before restoration; G4 (10SAs): similar procedures to G3, but applied 10SA, in aqueous solution formulation. The 15HP-TiO2 was applied on buccal and lingual surfaces of the crown tooth and inside the pulp chamber and photoactivated by LED-laser. Between each bleaching session, the teeth were maintained in artificial saliva, at 37oC, for 7 days. In sequence, the teeth were submitted to fracture resistance testing using an eletromechanical machine test. The data was analyzed using Kruskal Wallis test (p = 0.05) Results: There are no differences significant among the groups in relation to fracture resistance of endodontically treated teeth (p>0.05). Conclusions: The use of 10% sodium ascorbate, in gel or aqueous solution formulations, did not interfered on the fracture resistance teeth after dental bleaching using 15HP-TiO2 and LED-laser photoactivation.
Keywords: Tooth bleaching; Peroxides; Endodontics; Antioxidants; Tooth fractures